ANALISIS BIAYA PEMELIHARAAN ALAT-ALAT PRODUKSI DENGAN PENDEKATAN TPM (TOTAL PRODUCTIVE MAINTENANCE) ( Studi Kasus Di PT. Kalbe Milko Indonesia) - Palah , Ahmad Miptahul; Setiawan, Ade Budi; Melani, Maria Magdalena (Komunitas Manajemen Kompetitif, 2024)
Machine maintenance costs are costs incurred by the company in an effort to maintain and maintain the machine so that it can function according to the company's plan. Sources of data used in this study are primary data and secondary data, namely the data obtained directly include company documents. The data used in this study where the authors include data related to the maintenance costs of production equipment. This study aims to analyze the maintenance costs of production equipment with the TPM (Total Productive Maintenance) approach at PT. Kalbe Milko Indonesia. Based on the results of the analysis, it shows that the cost of maintaining production equipment after the implementation of TPM for the 2019 period, the efficiency value of all machines is -5.63%, still not efficient where the realization of costs is still greater than the budget, with a difference of (Rp, 56.352.105,00). And for the 2020 period, the imposition of maintenance costs on production equipment resulted in an efficient value of 17.25%, which resulted in an efficiency value of Rp, 172.544.859,56 TPM is good enough. The factors that cause costing before and after the implementation of TPM are five factors, namely human factors, material factors, machine factors, method factors and environmental factors. Keywords : Analysis of maintenance costs, Total productive maintenance, Cost efficiency.